Challenges of teaching multilingual students in tertiary education - Ilona Huszti; Ilona Lechner (Educational Challenges)
Purpose. This study investigates the challenges faced by teachers of multilingual learners at the Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education in Ukraine. The college serves a diverse student population, including native Ukrainian speakers and Hungarian speakers, as well as speakers of other languages, creating a complex and dynamic multilingual learning environment. This research aims to understand the specific challenges faced by teachers in navigating this linguistic diversity to support all students' academic success.